PENINGKATAN KUANTITAS PRODUKSI UKM KAOS OBLONG BERMITRAKAN IBM UNMAS DENPASAR - Ekayanti, Ni Wayan; Atmaja, Ni Putu Cempaka Dharmadewi; Setiawati, Gusti Ayu Dewi (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2017)
Taman Sari is a seam effort done by the owner of this business. Tailor Taman Sari has obstacles in the process of finishing products in the form of T-shirts, that is not able to provide a pattern of stitching chain sticks on the neck of the T-shirt that is the product of this seam effort. In addition, this stitching business always hire printing services in designing text that must be printed on the product, and printing services are in Denpasar, thus making the cost, time and energy to be ineffective. To overcome this, the team of IbM Unmas Denpasar helped this effort by providing chain sticks and a set of computer graphics. The efficiency of chain sticks on the productivity of Taman Sari tailor business is measured by using an open questionnaire containing the production amount for 4 months. The result of descriptive analysis showed an increase of quantity of Taman Sari tailor's shirt production for 4 months, but the result of statistic analysis showed no significant difference (p <0,068 *), this was due to the limitations of the sample studied. From the research results can be concluded that with the existence of chain sticks machine, the effectiveness of the production of Tailor Taman Sari can be improved.